2010
DOI: 10.1111/j.1750-2659.2010.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Original Article: Highly conserved cross‐reactive CD4+ T‐cell HA‐epitopes of seasonal and the 2009 pandemic influenza viruses

Abstract: Please cite this paper as: Duvvuri et al. (2010) Highly conserved cross‐reactive CD4+ T‐cell HA‐epitopes of seasonal and the 2009 pandemic influenza viruses. Influenza and Other Respiratory Viruses 4(5), 249–258. Background The relatively mild nature of the 2009 influenza pandemic (nH1N1) highlights the overriding importance of pre‐existing immune memory. The absence of cross‐reactive antibodies to nH1N1 in most individuals suggests that such attenuation may be attributed to pre‐existing cellular immune respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 67 publications
1
36
0
Order By: Relevance
“…That study found only two main sets of core motifs that would be beneficial to include in vaccines (14) to induce generic immune responses to influenza viruses. The HA T-cell epitopes of seasonal and 2009 pandemic strains have also shown a significant level of conservation (12).…”
Section: Seroprevalence Before and After The 2009 Influenza A(h1n1) Pmentioning
confidence: 99%
“…That study found only two main sets of core motifs that would be beneficial to include in vaccines (14) to induce generic immune responses to influenza viruses. The HA T-cell epitopes of seasonal and 2009 pandemic strains have also shown a significant level of conservation (12).…”
Section: Seroprevalence Before and After The 2009 Influenza A(h1n1) Pmentioning
confidence: 99%
“…Based on these studies, as well as our survey of human CD4 T cell reactivity to H7 HA (24), we speculated that the explanation behind the generally poor immunogenicity of avian HA relative to isolates from seasonal H1 and H3 HA proteins lies with the composition of the CD4 T cell memory compartment. Most humans have abundant CD4 T cell memory to epitopes contained within seasonal HA proteins (25,26), suggesting that it is this difference in the host that accounts for the overall ineffectiveness of avian vaccines. This contrasts with the speculation that avian HA proteins are inherently poorly immunogenic or have generalized deficits in T cell epitopes.…”
Section: Resultsmentioning
confidence: 99%
“…In order to do this, we utilized mouse models of vaccination, as virtually all human subjects have existing memory to seasonal H1N1 and H3N2 (25,26). We designed experiments to identify the number and abundance of MHC-II epitopes contained within H1, H3, H5, and H7 HA proteins that were recognized by CD4 T cells in an unbiased and comprehensive way.…”
Section: Resultsmentioning
confidence: 99%
“…The HA2 subunit, on the other hand, is more conserved among the different HA subtypes. Recently, an in silico study was done to evaluate the presence of cross-reactive T cell epitopes in the HA of seasonal influenza H1N1 and H3N2 viruses and the novel pandemic H1N1 virus (20). Duvvuri and colleagues found that CD4 ϩ T cell epitopes within different H1N1 strains were significantly conserved, while there were fewer conserved epitopes between the H3 and H1 subtypes (20).…”
mentioning
confidence: 99%
“…Recently, an in silico study was done to evaluate the presence of cross-reactive T cell epitopes in the HA of seasonal influenza H1N1 and H3N2 viruses and the novel pandemic H1N1 virus (20). Duvvuri and colleagues found that CD4 ϩ T cell epitopes within different H1N1 strains were significantly conserved, while there were fewer conserved epitopes between the H3 and H1 subtypes (20). Although their findings suggest that cross-reactive T cells recognizing an epitope across all the different HA subtypes may be elusive, there are regions in the HA2 subunit, in particular the fusion peptide sequence, that are highly conserved in all the different HA subtypes (15).…”
mentioning
confidence: 99%